Ethics, Personal Image, and Disinformation in the Era of Deepfakes - Fernández Fernández, Ángel; Martínez de Bartolomé Rincón, Ireide; Morgado Aguirre, Borja (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
Digital visual culture’s growing importance poses questions about image curation, rights, and privacy. Deepfakes intensify these challenges by enabling unprecedented audiovisual manipulation. This article critically examines the ethical, legal, and social repercussions of creating and distributing deepfakes, highlighting serious identity fraud risks. It also explores digital platforms’ regulatory measures designed to detect and restrict such content, underscoring the urgent need for explicit ethical standards. Additionally, the text addresses how deepfakes can perpetuate biases and discriminatory narratives, further eroding trust in visual information and reinforcing harmful stereotypes in the collective imagination. Ultimately, such manipulations demand robust governance to safeguard individual rights.